THE VALIDTY OF CREDIT AGREEMENT WITH COLLATERAL LAND AND BUILDING LETTER C - Dyah Ochtorina Susanti; Herowati Poesoko; Nuri Hidayati (NOTARIIL Jurnal Kenotariatan, 2019)
This study aims to determine the legality of credit agreement made with a guarantee of land and building proof of ownership of Letter C without the existence a Power of Attorney Charging Mortgage (SKMHT), Giving Deed Mortgage (APHT), and Mortgage Certificate (SHT). This study used a normative juridical research method with a statutory approach, conceptual and case. The credit agreement that has been made is stated and affects the law with the agreement that among the creditors (PNM) and the debtor (Komsatun) followed by the completion of the investment object, this was only in accordance with the 1320 Civil Servants Court. As for land and building of Letter C which was made as a courtesy agreement credit is displayed nothing happens and canceled as for law becase is not following madate paragraph 10 (3) UUHT, that letter C land to be used as a mortgage then the dependent can still be possible while giving it at same time with the process of applying for a land mortgage. Based on the result of the study, it can be concluded that the Credit agreement which made by the ownership of letter C of land and buildings guarantee without any binding for the notarial deed/PPAT in form of SKMHT, APHT, and SHT is official and binding according to law. Because of the credit agreement which already made according by agreement by the creditor (Bank PNM Ulam) and the debtor (Komsatun) followed by submission of money as an agree-ment project.